2022
DOI: 10.1001/jamainternmed.2022.1118
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Related Disorders of Family Members of Patients Admitted to the Intensive Care Unit With COVID-19

Abstract: IMPORTANCEThe psychological symptoms associated with having a family member admitted to the intensive care unit (ICU) during the COVID-19 pandemic are not well defined.OBJECTIVE To examine the prevalence of symptoms of stress-related disorders, primarily posttraumatic stress disorder (PTSD), in family members of patients admitted to the ICU with COVID-19 approximately 90 days after admission.DESIGN, SETTING, AND PARTICIPANTS This prospective, multisite, mixed-methods observational cohort study assessed 330 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 37 publications
3
39
0
4
Order By: Relevance
“…Visitor access to Australian hospitals was initially prohibited when the first cases of COVID-19 appeared in March 2020, with limited exceptions for patients at end-of-life. A duality of harm was caused to patients, families and staff by rigid visitation policies consistent with findings in other research ( [18] , [19] , [20] , [21] ). In the following months, as the number of cases in the community decreased, restrictions were eased in line with World Health Organization recommendations ( 22 ).…”
Section: Introductionsupporting
confidence: 87%
“…Visitor access to Australian hospitals was initially prohibited when the first cases of COVID-19 appeared in March 2020, with limited exceptions for patients at end-of-life. A duality of harm was caused to patients, families and staff by rigid visitation policies consistent with findings in other research ( [18] , [19] , [20] , [21] ). In the following months, as the number of cases in the community decreased, restrictions were eased in line with World Health Organization recommendations ( 22 ).…”
Section: Introductionsupporting
confidence: 87%
“…The individual possibility of attending either a FamHC or SGC is also important for recovery and maintaining family functioning. Even if the family is a unit, it is also defined by individuals having different needs for support during and after ICU care (Amass et al, 2022;de Ridder et al, 2021b;Rydwik et al, 2021). The quantitative analysis in studies II and IV showed that family functioning was mostly healthy two months after the ICU care, as well as family hardiness in study II.…”
Section: Results Discussionmentioning
confidence: 99%
“…A higher risk at developing PTSD was also seen in family members of COVID-19 ICU patients (Azoulay et al, 2022). Three months after the patient's admission with COVID-19 to the ICU the family members with higher scores of PTSD described feelings of distrust and concern about the need to take clinicians' information at face value without being present to see for themselves how the patient was feeling and if the care was successful (Amass et al, 2022).…”
Section: Covid-19mentioning
confidence: 97%
“…Stress has had a profound effect on family members, workers, and communities affected by the suffering or loss of life brought about by the pandemic. A recent study found that family members had significant symptoms of posttraumatic stress disorder (PTSD) months after the admission of a loved one to an intensive care unit and that these neuropsychological symptoms were significantly associated with ethnicity and gender [ 159 ]. Thus, considering psychosocial stress could help elucidate how disparities can contribute to the neuropathogenesis of COVID-19 and to outcomes in both patients and their communities.…”
Section: Additional Factors Impacting Neurological Effects Of Covid-19mentioning
confidence: 99%